Perbandingan Pemahaman Konsep dan Kemampuan Berpikir Kritis Melalui Model Pembelajaran Discovery Learning dan Direct Instruction - Istiqamah, Istiqamah; Sugiarti, Sugiarti; Wijaya, Muhammad (Chemistry Education Review (CER), 2019)
The research aims to discovering the description of understanding concept critical thinking skills of students, the difference of understanding concept critical thinking skills of student, and the correlation between understanding concept and critical thinking skills of students who were taught using discovery learning model and direct instruction on reaction rate material in grade XI MIA at SMAN 8 Takalar. The study was conducted at SMAN 8 Takalar with two classes as research subjects, class XI MIA 1 taught by using discovery learning model and class XI MIA 2 taught by using direct instruction on reaction with 25 students each. Data were analyzed descriptively and inferentially. The results of the study reveal that 1) the understanding concept on class taught by using discovery learning model was in good category; whereas class taught by using direct instruction model was in moderate category; 2) the critical thinking skills of both classes were in critical categories. Therefore, the conclusions of the study are (i) the understanding concept of students who were taught by using discovery learning model had gain average higher than the ones using direct instruction model, (ii) the critical thinking skill of student who were taught using discovery learning model had gain average higher than the ones taught using direct instruction learning model, (iii) there was correlation between understanding concept and critical thinking skill of students taught by using discovery learning model and direct instruction learning model.